الخطاب المعتدل واثره على التعايش السلمي في الفقه الاسلامي - علي, جمعة حسين; داود, ساجدة علاوي; النائلي, محمد فرحان عبيد; عبد النبي, عمار منصور; خضير, علي عبود; صالح, عمار باسم (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
One of the most important things that societies in the world are looking for is enhancing societal security between them and other peoples, which the research tried to highlight, and that religious discourse must focus on equality in rights and duties for every member of society. The research confirms that societal security is the will of the people of different religions and civilizations in order for security and peace to prevail and for humanity to live in an atmosphere of brotherhood and acquaintance that applies to all human beings without exception. The research highlighted a number of facts after the introductions that preceded it were addressed. The research clarified the importance of activating the rejection of extremism in society and the effective mechanism to reduce it. The concept of societal security is considered one of the modern concepts whose wording is not. The research showed that religious discourse is characterized by moderation, which is the lack of fanaticism towards a particular sect, but rather adopting what is beneficial from our Islamic heritage, and that rejecting extremism has an impact in establishing an important goal of Sharia law, which is preserving people’s minds from descending towards corrupt perceptions and deviant ideas. The research concluded that Islamic societal security is a necessary need, without which life would not be possible. Rather, it is the basis of security for societies in general, and it is the most important of them, and the basis of their existence and continuity, as it is an essential element in preserving the five necessities that Islamic law came to protect.